Thinking with co-creation: meaningful engagement and regeneration in deeper adaptation to climate change - Korsbrekke Mari Hanssen; Gram-Hanssen Irmelin; Beitnes Synnøve; Holm Tara; Meyer-Habighorst Christiane; Dudzińska-Jarmolińska Agnieszka; Łatała Katarzyna; Jasińska Katarzyna (Miscellanea Geographica: Regional Studies on Development, 2025)
Whether we regard the 1.5 °C target as feasible, climate change adaptation can bring the most favourable outcomes when supported by strategies that increase democratic participation while embracing diverse perspectives and worldviews that highlight the potential for societal change. Rooted in values of equity, justice, mutual aid, creativity and compassion, flexible co-creation approaches show promise in accommodating more caring conversations and actions. In this article, we share insights on factors shaping engagement quality in co-creative adaptation across different cultural contexts. We identify common characteristics that support high levels of engagement, deeper care and meaningful participation over time. These include 1) ‘arts of noticing’, 2) strengthening community networks and 3) cultural and social-ecological reproduction and restoration. These modes of engagement can provide nuance in the conversation on care and deep adaptation with ways to meaningfully navigate the social-ecological crisis on an increasingly damaged planet.